Land Snails from Pine and Big Black Mountains, Kentucky - Branley A. Branson; Donald L. Batch (Hello World!, 1968)
In 1900, Pilsbry marshalled molluscan evidence to demonstrate the relatively distinctive nature of the fauna in the Cumberland Plateau as contrasted with that of the eastern mountains (Roan Mountain to the Great Smokies). He considered the broad valley of East Tennessee to be a partial barrier to intermingling of the two faunas. Collections in 1967 by the present authors tend to ameliorate the barrier concept, or at least extend the Smoky Mountain fauna into Kentucky.